Pengalaman Guru PAI dalam Membangun Sikap Toleransi Beragama di Sekolah Minoritas Muslim Kota Medan - Muhammad Sofwan; Masganti Sitorus; Ahmad Syukri Sitorus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the understanding and implementation of religious tolerance values ​​by Islamic Religious Education (PAI) teachers in schools where Muslim students are a minority—specifically, SMA Free Methodist 1 Medan and SMA Free Methodist 2 Medan. The research employs a qualitative approach utilizing a comparative case study design and narrative inquiry. Data were collected through participant observation, in-depth interviews with PAI teachers, school principals, and students, as well as document analysis. Data analysis was conducted interactively through stages of data condensation, data display, and conclusion drawing, alongside cross-site analysis. The findings indicate that PAI teachers at both schools share a consistent understanding of religious tolerance: an attitude of accepting and respecting differences without compromising Islamic faith. This understanding is grounded in Quranic references (such as Surah Yunus: 99, Surah Al-Kafirun: 6, and Surah Al-Ma'idah: 8), the thoughts of contemporary Islamic scholars, and the values ​​of religious moderation (*wasathiyah*). Tolerance is implemented through contextual, dialogic, and humanistic teaching methods that relate to the students' reality as a minority group. Instructional strategies include group discussions, case studies, reflection, and the use of digital media. Factors supporting this success include an inclusive school culture, accommodating foundation policies, the provision of worship facilities or dedicated PAI spaces, and harmonious relationships among the academic community.